Analysis of the potential for expanding the use of cargo bikes in the Czech Republic - Seidlová, Andrea; Ledvinová, Michaela (Kaunas University of Technology, 2024)
The article deals with the factors that influence people's motivation to use cargo bikes as an alternative to cars. Cargo bikes are means of transport with a minimal impact on the environment, and their wider use can contribute to improving sustainable mobility in cities. In the Czech Republic, bicycles are quite popular, especially for recreation and sports. In regions with suitable conditions, bicycles are often used for trips to work and, to a lesser extent, for shopping. It can therefore be assumed that there is a certain potential for wider use of cargo bikes, which are currently used rather rarely. Based on a questionnaire survey, the article examines the circumstances under which respondents would be willing to use a cargo bike. The aim is primarily to define the potential user of a cargo bike and the conditions for increasing the motivation to use cargo bikes.
Analýza potenciálu pro zvýšení využívání nákladních kol v České republice
Keywords: cargo bikes; sustainable mobility; nákladní kola; udržitelná mobilita